Eat the ones you love - Griffin, Sarah Maria (Tor Publishing Group, 2025)
"A twisted, tangled story about workplace love-affairs, and plants with a taste for human flesh. During a grocery run to her local shopping center, Shell Pine sees a 'HELP NEEDED' sign in a flower shop window. She's just left her fiancé, lost her job, and moved home to her parents' house. She has to make a change and bring some good into her life, so she goes inside and takes a chance. Shell realizes right away that flowers are just the good thing she's been looking for, as is Neve, the beautiful florist who wrote the sign asking for help. The thing is, Neve needs help more than Shell could possibly imagine. An orchid growing out of sight in the heart of the mall is watching them closely. His name is Baby, and the beautiful florist belongs to him. He's young, he's hungry, and he'll do just about anything to make sure he can keep growing big and strong. Nothing he eats - nobody he eats - can satisfy him, except the thing he most desires. Neve. He adores her and wants to consume her, and will stop at nothing to eat the one he loves. This is a story about possession, and monstrosity, and working retail. It is about hunger and desire, and other terrible things that grow"--